If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8x = 2 + -5 + 5x + 5x Combine like terms: 3x + 8x = 11x 11x = 2 + -5 + 5x + 5x Combine like terms: 2 + -5 = -3 11x = -3 + 5x + 5x Combine like terms: 5x + 5x = 10x 11x = -3 + 10x Solving 11x = -3 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 11x + -10x = -3 + 10x + -10x Combine like terms: 11x + -10x = 1x 1x = -3 + 10x + -10x Combine like terms: 10x + -10x = 0 1x = -3 + 0 1x = -3 Divide each side by '1'. x = -3 Simplifying x = -3
| 5/6x-7/6=4 | | r=.066*3000(1-0.59*.066) | | 25s^2-81= | | 3(2y-7)=3 | | (4x^2+8x/4x+5)-(7x+5/4x+5) | | (x-4)^2/3=16 | | -3x+3+4x=5 | | 9k=2.34 | | 1/x+5/x-4=0 | | -6(x+9)-6+3x=25 | | b-26/17 | | 2(x-7)=5x-12 | | -10+7x+5x=-118 | | 13-28/x=4+8/x | | 4(x+7)=2x+31 | | 9(x-4)/3x | | 8.34x+41.7=83.4 | | (2/3)Y+(1/2(Y-3))=(Y+1)/4 | | 5(x+1)/25 | | 4x-50=190 | | 3z=2+z-2 | | (2Y/3)+(1/2(Y-3))=(Y+1)/4 | | 2/11x+1/2=4/9-9/11x+4/9 | | 6x+20=320 | | 25y+13=2y^2 | | x/2-500=3x/7 | | 18x-x^2=0 | | 2/11x+1/2=4/9-9/11x-4/9 | | 9(x+4y)= | | 0.795x^2-0.908x+1.838=0 | | 4x+6=4+2(2x+1) | | x^3-9x^2-25x-23=0 |